Pseudotumor Cerebri in a Child With Familial Mediterranean Fever - Faruk İNCECİK,; Özlem M. HERGÜNER,; Mustafa YILMAZ,; Şakir ALTUNBAŞAK, (Archives of Rheumatology, 2015)
Familial Mediterranean fever is an autosomal recessive polysystemic disease characterized by attacks of relapsing and self-limiting fever, peritonitis, pleuritis and arthritis. Neurologic involvement is rare but serious in Familial Mediterranean fever. Headache, seizures, demyelinating lesions, stroke, posterior reversible leukoencephalopathy syndrome, aseptic meningitis, convulsions, and cranial neuropathy have been reported in the literature. In this article, we present the first Familial Mediterranean fever and pseudotumor cerebri association in a child and discuss the pertinent literature.